Entrepreneurship Competence as a Determinant of MSME Performance: Literature Study - muchtadin much (Business and Entrepreneurial Review, 2022)
Efforts to develop MSMEs in a sustainable manner are certainly not easy and are influenced by various internal and external factors. As many as 80% of companies that are just starting out have failed in the first year and the probability of failure of small businesses in Indonesia reaches 78%. Therefore, it takes good competence from entrepreneurs to reduce the possibility of business failure and improve the performance of MSMEs themselves. This study aims to determine whether entrepreneurial competence is able to improve business performance of Micro, Small and Medium Enterprises (MSMEs) through a literature review. The data are taken from eleven national journals indexed by sinta and six journals indexed by scopus in the last ten years. This study concludes that entrepreneurial competence is able to improve the performance of MSMEs. The literature review covers a wide variety of sectors and aspects of measurement. Future research is expected to use a wider population such as a province or country, be longitudinal and add control variables such as gender, age, size of business, education level.